An analysis of speech act of Omar Mukhtar's utterances in lion of the desert movie - Syukri Rizki; Jelena Golubović (Universitas Islam Negeri Banda Aceh, 2020)
Movies are brilliant choices to be subjects of discourse analysis since they bear resemblance to real-life phenomena. Lion of The Desert is one of the movies that actualizes the use of the English language as the dialogue and presents Islamic historical values as its content. Among a myriad of sub-disciplines of discourse analysis, this paper attempts to investigate speech act phenomena in the utterances of Omar Mukhtar, the main character of the movie. The discourse analysis is conducted on his utterances in order to extract the types of speech acts he employs. Primary data sources include the movie video file and its script. We execute several procedural steps of extracting the data, commencing with watching the movie while reading its script; re-watching it to identify the aspects like voice, intonation, and mimics; interpreting, and classifying the types of speech acts in accordance with the classification procedure of John R. Searle’s speech act theory. The findings revealed four types of speech acts, namely, representative, directive, commissive, and expressive, being identified and classified in Mukhtar’s utterances. The most frequently used type of speech act was representative, which is performed in 56 utterances, followed by a directive act which appears in 53 utterances. Commissive and expressive speech acts emerge in 9 and 7 utterances respectively.